Definition of timing in the control of the 1st generation Lasioderma serricorne adults, inside tobacco stores, based on the development of the oocytes - Papadopoulou, Smaragdi C. (ENTOMOLOGIA HELLENICA, 2006)
The development of the oocytes of pupae, females inside the pupal cell and after emergence of Lasioderma serricorne (F.) (Coleoptera: Anobiidae) was studied by dissecting their abdomen. The time of oocytes maturation as well as that of the starting of their oviposition, in combination with the insect’s developmental threshold was determined, aiming to time the 1st effective control against the emerging adults of the 1st generation.